Cognitive behavioral psychotherapy (CBT) — targets in working with jealousy problems - R. Leahey; A. V. Vasileva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
The article considers the main targets for jealousy based individual maladaptation and couple stress psychotherapy. The main relationship system development features and early attachment types responsible for later intensive jealousy experiences are defined. The cognitive processing and biases assessment targets are recommended alternative cognitive strategies are proposed. The article presents main techniques and exercises of the metacognitive CBT model.